Effects of Faith Integration Activities on Students' Epistemologies in Introductory Physics Classes. Issue 4 (5th August 2021) - McCoy, Bradley K.
Abstract: Integrating faith with academic disciplines should result in enrichment of students' perspectives on both the discipline and their faith. This quasi-experimental pilot study examines how faith integration activities in introductory physics classes affected students' epistemologies, defined as their beliefs about the nature of knowing and learning. The faith integration activities consisted of daily in-class discussions of characteristics of scientists, including comparisons and contrasts of typical traits of scientists with traditional Christian virtues. Changes in students' epistemologies throughout their first semester of introductory physics were measured using the Epistemological Beliefs Assessment for the Physical Sciences (EBAPS) survey. Previous research has shown that in a typical introductory physics class, students' epistemological beliefs become less expert-like. Comparing students who received the intervention with those that did not, students' EBAPS scores decreased without the intervention, although the typical decreases did not occur with the intervention. The largest improvement occurred on students' beliefs on the source of ability to learn, which was emphasized in the in-class discussions. Moreover, students in the first quartile by EBAPS pre-score showed decreases in the source of ability to learn score without intervention, but gains in the source of ability to learn axis with intervention. These results indicate that the faith integration intervention produced results of value to the discipline by preventing the typical degradation in students' epistemologies, with the largest benefit to students at risk of not persisting in STEM because of epistemological barriers.